Penggunaan Fuzzy Logic Control Untuk Kestabilan Solar Sel Dengan Menggunakan Matlab - Firman Yudianto; ima kurniastuti; Nahdia rupawanti BR (Universitas Islam Lamongan, 2021)
Solar cell are currently needed and have been widely used in Indonesia asan alternative energy to help supply energy. This energy reliability will be moreeffective if the maximum power usage is monitored by measurement andsimulation. FLC is carried out to test the correctness of the value of thesimulink module block with solar cell panels, namely short circuit currenttesting and open circuit voltage testing. The simulation was carried out withirradiation of 1000 W/m2 and a temperature of 25 degrees Celsius withtechnical data of solar cell panels.Result of test the solar panel system that is connected to the load usingthe MPPT system, it is carried out with the same irradiation and temperaturevalues as in the simulation without MPPT. In the system also installed a load inthe form of a resistor. Based on the test results without MPPT, to reach themaximum power point, the FLC output is expected to be close to the value ofthe duty cycle of 1% to 35%.